Case report: Intraneural perineurioma in dogs: a case series and brief literature review - Yin, Ji-Hang; Sexton, Brittani; Jukier, Tom; Yanke, Amy B.; Holland, Merrilee; Miller, Andrew D.; Stranahan, Lauren; Hoffmann, Aline Rodrigues; Sandey, Maninder (Frontiers in Veterinary Science, 2024)
Intraneural perineurioma is an exceptionally rare neoplasm in animals. This case study comprises a series of three cases and a brief literature review focusing on canine intraneural perineurioma. The pathologicaland immunohistochemical findings are documented, revealing that canine intraneural perineurioma frequently affects adult dogs aged between 3 to 10 years old, with a male predominance. Clinical signs associated with intraneural perineurioma in dogs include spinal pain, lameness, and paresis, resulting from the involvement of spinal nerve roots of the pelvic limbs, brachial plexus, or distal part of the median nerve. Most neoplasms had characteristic pseudo-onion bulb patterns on histopathology. Neoplastic perineurial cells, in most cases, expressed laminin and claudin-1, and NF200 consistently highlighted the central axon. While the immunohistochemical (IHC) profile of intraneural perineurioma in veterinary medicine remains incompletely characterized, the available IHC data from all reported cases suggest that a combination of laminin and claudin-1 immunomarkers, along with distinctive histological features, can assist in establishing a definitive diagnosis of intraneural perineurioma.